Philosophy of nonviolence revolution, constitutionalism, and justice beyond the Middle East - Mallat, Chibli (Oxford University Press, 2015)
Philosophy of Nonviolence maps out a system articulating nonviolence in the revolution, the rule of constitutional law it yearns for, and the demand for accountability that inspired the revolution in the first place.